1993
DOI: 10.1111/j.1699-0463.1993.tb00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Yersinia enterocolitica infection in rodents: A model for human yersiniosis

Abstract: enterocolitica infection in rodents: A model for human yersiniosis. APMIS 101: 417429, 1993. Yersiniu enterocoliticu infection in humans causes a broad spectrum of diseases ranging from acute bowel disease to extraintestinal manifestations such as reactive arthritis, erythema nodosum and uveitis. During the last decade a fascinating part of the molecular biology of the pathogenicity of human pathogenic Yersinia species has been unraveled. Pathogenicity factors such as protein tyrosine phosphatase, protein k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
59
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 97 publications
3
59
0
Order By: Relevance
“…However, present mouse and rat models focus on systemic disease caused by yersiniae, i.e. septicaemic infections and post-infectious arthritis [24]. No simple animal models which entirely reproduce human intestinal disease due to Y.…”
Section: Discussionmentioning
confidence: 99%
“…However, present mouse and rat models focus on systemic disease caused by yersiniae, i.e. septicaemic infections and post-infectious arthritis [24]. No simple animal models which entirely reproduce human intestinal disease due to Y.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are some reports on the involvement of M cells in the initial step of the infection with enteric pathogens [1][2][3][4][5], the formation of the pseudopodium as big as that demostrated in the present study is not known. Therefore, the pseudopodia may have been developed specifically for uptake of the killed bacteria.…”
mentioning
confidence: 68%
“…A thinner pseudopodium was observed in M It has been shown that microfold (M) cells in the epithelium of the Peyer's patches dome region are involved in the initial stage of the invasion of enteropathogens [2,8,11]. An association of M cells with the intestinal invasion of Yersinia known as an agent of human gastroenteritis is known [1,[3][4][5]. The mechanism of the invasion of these pathogens into the M cells, however, is still obscure.…”
mentioning
confidence: 99%
“…Several studies have highlighted differences in the resistance of various mouse strains to intravenous infection with Y. enterocolitica. (Hancock et al 1986, Heesemann et al 1993, Autenrieth et al 1994. By the other hand, Handley et al (2004) working with different strains of inbred mice related that the animals presented no differences in 50% lethal dose ( LD 50 ) following oral infection with Y. enterocolitica.…”
Section: Discussionmentioning
confidence: 99%
“…The latter has been well documented in Y. enterocolitica (Quan et al 1974, Carter & Collins 1974, Alonso et al 1975, 1978, Une 1977, Falcão et al 1984, Apfel & Noleto 1991, Bauab & Falcão 1991, Heesemann et al 1993. However in Y. pseudotuberculosis, only a few studies have shown in vivo infection, and the kinetics has not been studied.…”
mentioning
confidence: 99%